2011
DOI: 10.1038/nm.2336
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of Fmrp in adult neural stem cells disrupts hippocampus-dependent learning

Abstract: Deficiency in fragile X mental retardation protein (FMRP) results in fragile X syndrome (FXS), an inherited form of intellectual disability. Despite extensive research, how FMRP deficiency contributes to the cognitive deficits in FXS is unclear. We have previously shown that Fmrp-null mice exhibit reduced adult hippocampal neurogenesis. Since Fmrp is also enriched in mature neurons, we explored the functional significance of Fmrp expression in neural stem and progenitor cells (aNSCs) and its role in adult neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
270
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(288 citation statements)
references
References 58 publications
18
270
0
Order By: Relevance
“…Recently, Guo et al, 2011 clearly demonstrated the functional significance of adult neurogenesis using adult nestin-expressing precursor cell-specific conditional deletion of the fragile X mental retardation protein (Fmrp; responsible for fragile X syndrome) in mice. Moreover, disrupted in schizophrenia 1 (DISC1; a protein implicated in major mental disorders) was shown to promote proliferation of neural progenitors through the GSK3␤/␤-catenin pathway, and GSK3␤ inhibitor rescued the proliferation and behavior defect caused by DISC1 knockdown in adult mice (Mao et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Guo et al, 2011 clearly demonstrated the functional significance of adult neurogenesis using adult nestin-expressing precursor cell-specific conditional deletion of the fragile X mental retardation protein (Fmrp; responsible for fragile X syndrome) in mice. Moreover, disrupted in schizophrenia 1 (DISC1; a protein implicated in major mental disorders) was shown to promote proliferation of neural progenitors through the GSK3␤/␤-catenin pathway, and GSK3␤ inhibitor rescued the proliferation and behavior defect caused by DISC1 knockdown in adult mice (Mao et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we identified several genes in this group that had been shown previously to be downregulated in schizophrenia patients. For example, TTR has been reported recently to be significantly decreased in the CSF of schizophrenia patients (Huang et al, 2006). HTR2C and SULF1 have been demonstrated to be decreased in schizophrenic prefrontal cortex (Castensson et al, 2005;Narayan et al, 2008), and another group reported that the expression of Ace was decreased in their brains (Arregui et al, 1979).…”
Section: Decreased Expression Of Several Schizophrenia-associated Genmentioning
confidence: 99%
See 1 more Smart Citation
“…However, by age 3-4 months, BDNF expression in the murine hippocampus is reduced compared to WT (52,55). Defects in hippocampal neurogenesis lead to cognitive deficits in the adult Fmr1 KO (56) and correlates with the hippocampal neurogenesis defects observed in individuals with FXS (57).…”
Section: Serotonin and Up-regulation Of Brain Derived Neurotropic Facmentioning
confidence: 99%
“…In addition, patients who exhibit mosaicism of either the CGG repeat size or DNA methylation levels on the FMR1 gene are able to make some FMRP and present with milder clinical symptoms [18]. Furthermore, restoring FMRP expression specifically in adult neural stem cells (NSCs) rescues hippocampus-dependent learning deficits in FMRP-deficient KO mice [19]. These observations suggest that partialrestoration ofFMRP even after birth could be clinically beneficial for patients with FXS.…”
Section: Introductionmentioning
confidence: 98%